2018
DOI: 10.1021/acs.chemrev.8b00277
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Wall Recycling of the Gram-Negative Bacteria and the Nexus to Antibiotic Resistance

Abstract: The importance of the cell wall to the viability of the bacterium is underscored by the breadth of antibiotic structures that act by blocking key enzymes that are tasked with cell-wall creation, preservation, and regulation. The interplay between cell-wall integrity, and the summoning forth of resistance mechanisms to deactivate cell-wall-targeting antibiotics, involves exquisite orchestration among cell-wall synthesis and remodeling and the detection of and response to the antibiotics through modulation of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
193
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(197 citation statements)
references
References 410 publications
(857 reference statements)
1
193
0
3
Order By: Relevance
“…The OM is made up of a unique asymmetrical lipid bilayer, with the inner leaflet consisting of phospholipids and the outer leaflet composed by lipopolysaccharide. The OM can act as a barrier to prevent drugs from reaching intracellular targets, rendering the Gram‐ E. coli presents a relatively high resistance to minocycline . Nevertheless, it is reported that the OM is sensitive to ROS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OM is made up of a unique asymmetrical lipid bilayer, with the inner leaflet consisting of phospholipids and the outer leaflet composed by lipopolysaccharide. The OM can act as a barrier to prevent drugs from reaching intracellular targets, rendering the Gram‐ E. coli presents a relatively high resistance to minocycline . Nevertheless, it is reported that the OM is sensitive to ROS .…”
Section: Resultsmentioning
confidence: 99%
“…Unlike Gram+ species, Gram‐ bacteria lack the thick peptidoglycan cell wall; instead, they possess an additional outer membrane (OM). Most antibiotics can hardly pass through the hydrophobic OM, resulting in their little inhibition effect to Gram‐ bacteria . Therefore, destroying the OM is an effective way to help antibiotics kill Gram‐ bacteria and acquire broad‐spectrum antibacterial abilities .…”
Section: Introductionmentioning
confidence: 99%
“…This scheme is a simplification. Ligand regulation of AmpR is more complex (and indeed, is not general from one bacterial genus to another) as is discussed elsewhere…”
Section: Abetting the β‐Lactam Antibiotics Against Gram‐negative Bactmentioning
confidence: 99%
“…The clinical importance of this connection cannot be overstated . The breadth of study of this β‐lactamase‐resistance response—from the molecular (antibiotic structure) to the macromolecular (protein‐ligand interaction, biochemical pathways) to the microbiological and the clinical—requires the medium of the comprehensive review . Here, we focus on the involvement of a family of important enzymes—the lytic transglycosylases—in peptidoglycan recycling and β‐lactamase induction …”
Section: Abetting the β‐Lactam Antibiotics Against Gram‐negative Bactmentioning
confidence: 99%
See 1 more Smart Citation